2023
DOI: 10.3390/brainsci13081202
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Insights into Sleep Disorders in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a common multidimensional neurological disorder characterized by motor and non-motor features and is more prevalent in the elderly. Sleep disorders and cognitive disturbances are also significant characteristics of PD. Sleep is an important physiological process for normal human cognition and physical functioning. Sleep deprivation negatively impacts human physical, mental, and behavioral functions. Sleep disturbances include problems falling asleep, disturbances occurring during sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 229 publications
0
7
0
Order By: Relevance
“…RBD is a sleep disorder characterized by abnormal motor behavior associated with dream mentation and loss of atonia during REM sleep [ 3 ]. Scientific attention over RBD has increased due to its association with α-synucleinopathies.…”
Section: Genes Involved In Pd Patients’ Sleep Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…RBD is a sleep disorder characterized by abnormal motor behavior associated with dream mentation and loss of atonia during REM sleep [ 3 ]. Scientific attention over RBD has increased due to its association with α-synucleinopathies.…”
Section: Genes Involved In Pd Patients’ Sleep Disordersmentioning
confidence: 99%
“…A recent meta-analysis study showed that PD patients with heterozygous GBA variants are at high risk of developing RBD. PD patients with GBA variants, like N370S and L444P, are at an even higher RBD risk than PD patients without these variants [ 3 , 12 ]. Moreover, in a recent study Perez-Lloret et al found that GBA _N370S_rs76763715 was associated with more frequent pRBD among PD patients.…”
Section: Genes Involved In Pd Patients’ Sleep Disordersmentioning
confidence: 99%
See 3 more Smart Citations